1979
DOI: 10.1007/bf00115589
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation times of molecular ions OH? in glasses at very low temperature

Abstract: This paper presents a detailed study of the temperature dependence of the longitudinal relaxation time T I and of the coherence time T e o[ a population of ionic molecular impurities in silica glass. Electric dipolar echoes taken in a temperature range 4-22 mK and a frequency of 370 MHz show that T I isgoverned by a one-phonon process; consequently T~ vanes hke T ; expertmental data show that Te also vanes hke T and thts m contradtctton wtth predictions which lead to T -e. The relaxation of the spontaneous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…The factor b defining the linear temperature dependence in (5.90) is in good agreement with that obtained via measurements of spontaneous echoes (Bernard et al (1979)), where b Rl 10 6 K-Is-I has been observed, and the echo measurements in Suprasil-I (Baier et al (1988)) where b Rl 2 X 10 6 K-Is-I has been found.…”
Section: As We Have Already Mentioned the Interaction Ofts's Is Weaksupporting
confidence: 83%
See 1 more Smart Citation
“…The factor b defining the linear temperature dependence in (5.90) is in good agreement with that obtained via measurements of spontaneous echoes (Bernard et al (1979)), where b Rl 10 6 K-Is-I has been observed, and the echo measurements in Suprasil-I (Baier et al (1988)) where b Rl 2 X 10 6 K-Is-I has been found.…”
Section: As We Have Already Mentioned the Interaction Ofts's Is Weaksupporting
confidence: 83%
“…5.1.7 [see e.g Bernard et al (1979), Kleiman et al (1987), Baier et al (1988), Enss et al (1990), Classen et al (1994), Esquinazi et al (1992), Esquinazi et al (1994), Rogge et al (1996b)]. 5.1.7 [see e.g Bernard et al (1979), Kleiman et al (1987), Baier et al (1988), Enss et al (1990), Classen et al (1994), Esquinazi et al (1992), Esquinazi et al (1994), Rogge et al (1996b)].…”
Section: Theoretical Approaches To the Relaxation Of Tunneling Systemsmentioning
confidence: 99%
“…The defect dipole electric coupling has been measured in dielectric absorption experiments and takes the value |d| = 0.3 − 3.3 Debye for silica [66]. Hence, for comparable mode volumes photons and phonons couple to defects with the nearly same strength.…”
Section: Theory Of Defect-phonon/defect-photon Interactions In Mmentioning
confidence: 99%
“…Even if they are required by consistency (see above and Ref. [24]), these two terms do not exist in the pionneering works accounting either for the small instationnarities [5] or for echo experiments [28], [29], [30]. In fact these two terms play a negligible role in the nonlinear susceptibility.…”
Section: Iii) Final Form Of the Bloch Equationsmentioning
confidence: 99%